IL-17 signaling components in bivalves: comparative sequence analysis and involvement in the immune responses - ROSANI, UMBERTO; VAROTTO, LAURA; VENIER, PAOLA; Gerdol M; Pallavicini A (Elsevier, 2015)
The recent discovery of soluble immune-regulatory molecules in invertebrates takes advantage of the rapid growth of next generation sequencing datasets. Following protein domain searches in the transcriptomes of 31 bivalve spp. and in few available mollusk genomes, we retrieved 59 domains uniquely identifying interleukin 17 (IL-17) and 96 SEFIR domains typical of IL-17 receptors and CIKS/ACT1 proteins acting downstream in the IL-17 signaling pathway. Compared to the Chordata IL-17 family members, we confirm a separate clustering of the bivalve domain sequences and a consistent conservation pattern of amino acid residues. Analysis performed at transcript and genome level allowed us to propose an updated view of the components outlining the IL-17 signaling pathway in Mytilus galloprovincialis and Crassostrea gigas (in both species, homology modeling reduced the variety of IL-17 domains to only two 3D structures). Digital expression analysis indicated more heterogeneous expression levels for the mussel and oyster IL-17 ligands than for IL-17 receptors and CIKS/CIKSL proteins. Besides, new qPCR analyses confirmed such gene expression trends in hemocytes and gills of mussels challenged with heat-killed bacteria. These results uphold the involvement of an ancient IL-17 signaling pathway in the bivalve immune responses and, likewise in humans, suggest the possibility of distinctive modulatory roles of individual IL-17s/IL-17 receptors. Overall, the common evidence of pro-inflammatory cytokines and inter-related intracellular signaling pathways in bivalves definitely add complexity to the invertebrate immunity.